Protease Inhibitor Phenotype BsaskatoonM Is Not Associated with Emphysema – A 20-Year Follow-Up Study - Ruzica Jokic; Kendra L Fisher; Donald W Cockcroft (Canadian Respiratory Journal)
OBJECTIVE: To investigate the association between the PiBsaskatoon variant of alpha-1 protease inhibitor (α1 Pi), present in the heterozygous state and the development of emphysema.